Analisis Perilaku Narsisme pada Siswa Kelas XII MIPA SMA Negeri 1 Tahun 2024 - Pratiwi, Rani Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Narcissism is an attitude that excessively involves oneself to the extent of neglecting the needs of those around them. Additionally, it is characterized by a sense of being more capable, unique, and special compared to others. In psychology, the term narcissism can be classified as a personality disorder. The primary issue addressed in this research is: How is the analysis of narcissistic behavior among the twelfth-grade science students at SMA Negeri 1 Sintang in 2024? The sub-issues are: (1) What are the characteristics of narcissistic behavior among the twelfth-grade science students at SMA Negeri 1 Sintang in 2024? (2) What factors contribute to narcissistic behavior among these students? (3) What efforts do guidance and counseling teachers undertake to help address narcissistic behavior among the twelfth-grade science students at SMA Negeri 1 Sintang in 2024? The method employed in this study is descriptive. The population for this research is the analysis of narcissistic behavior among the twelfth-grade science students at SMA Negeri 1 Sintang in 2024. This study utilizes a quantitative approach. Data collection techniques involve indirect communication, and the data collection instrument used is a questionnaire. Data analysis is conducted using percentage formulas. The results indicate that the analysis of narcissistic behavior among the twelfth-grade science students at SMA Negeri 1 Sintang is categorized as "High." Based on the above description, it can be concluded that the analysis of narcissistic behavior among the twelfth-grade science students at SMA Negeri 1 Sintang overall falls into the "High" category.